M - 1 = D + 1
2 * (D - 1) = M + 1
can you solve the rest as two equations with two variables?
M = D + 2
(2 * D) - 2 = M + 1
M = D + 2 substitute into
2 * D = M + 3
2 * D = (D + 2) + 3
2 * D = D + 5
Looks like D = 5.
So M = D + 2 = 7
Donkey has 5 and Mule has 7.
Check it out and see if it works.
2006-11-12 08:02:44
·
answer #1
·
answered by emilynghiem 5
·
0⤊
0⤋
Break down the sentences into equations:
"If one mule gave the donkey one bag, they would have the same number"
m - 1 = d + 1
Mule gave donkey one, so mule is -1, donkey got one, so donkey is +1
"If the donkey gave the mule one of his bags, the mule would have twice as many as the donkey."
2*(d - 1) = m + 1
Donkey gave mule one, so donkey is -1, mule is +1, mule is twice current donkey value, so (m+1) = 2*(d - 1)
Subtract the first equation from the second, and you get:
m+1 = 2(d - 1)
-(m-1 = d + 1)
_____________
2 = d - 3 => d = 5
m - 1 = d + 1 = 5 + 1 = 6
m = 7
2006-11-12 16:10:25
·
answer #2
·
answered by Absent Glare 3
·
0⤊
0⤋
donkey 5 mule 7
2006-11-12 16:31:16
·
answer #3
·
answered by dcmclaren77 1
·
0⤊
0⤋
the donkey had 5 bags and the mule has 7
2006-11-12 16:01:11
·
answer #4
·
answered by D.P 3
·
0⤊
0⤋
donkey has 2 mule has 4
2006-11-12 16:04:24
·
answer #5
·
answered by ArmyWife 2
·
0⤊
0⤋
This is a very simple problem, just write the two equations and then solve them. Assume that the donkey has d bags of grain to start and the mule has m bags of grain to start.
2006-11-12 16:00:43
·
answer #6
·
answered by rscanner 6
·
0⤊
0⤋
u are in 7th grade arent u?
donkey 5 mule 7
2006-11-12 16:06:52
·
answer #7
·
answered by asdrewq 1
·
0⤊
0⤋
5 and 7
2006-11-12 15:57:35
·
answer #8
·
answered by polloloco.rb67 4
·
0⤊
1⤋
the donkey carrys 4
the mule carrys 5
2006-11-12 16:00:16
·
answer #9
·
answered by 7
·
1⤊
1⤋
let m=bags on mule
and d= bags on donkey
so
m-1=d+1 so m = d+2 equation 1
and 2(d-1)=m+1 equation 2
substitution of equation 1 into equation 2 yields
2(d-1)=d+3 so 2d-2=d+3 so d=5 and m=7
2006-11-12 16:00:14
·
answer #10
·
answered by ? 7
·
0⤊
1⤋